Modelling Ports Investment and Island Economic Growth - Tukan, Marcus; Achmadi, Tri; Wijaja, Sjarief; Ciptomulyono, Udisubakti (IPTEK The Journal for Technology and Science, 2025)
The port is a gateway region's economy. Investment performance is important that an effective and efficient port to ensure smooth supply chain needs of the region and promote economic growth. This study aims to model the port investment relationship with economic growth. Quantitative analysis and econometric modeling is used in statistical testing, studies typically classified in two areas, namely: the north and south islands of Maluku. The northern and southern regions and the increase in the loading dock term investment to drive economic growth, but the number of visits relation ship with economic growth negative influence.